Rural and urban differences in quality of dementia care of persons with dementia and caregivers across all domains: a systematic review - Geneviève Arsenault-Lapierre; Tammy X. Bui; Mélanie Le Berre; Howard Bergman; Isabelle Vedel (BMC, 2023)
Abstract Background There are challenges in healthcare service delivery in rural areas, and this may be especially true for persons with dementia, who have higher needs to access to the healthcare system, and may have difficulties to commute easily and safely to these services. There is a growing body of literature regarding geographical disparities, but there is no comprehensive systematic review of geographical differences in persons with dementia across all domains of care quality. Therefore, the objective of this study is to conduct a systematic review of the literature on rural and urban differences in quality of dementia care outcomes of persons with dementia across all quality-of-care domains. Methods We performed a digital search in Ovid MEDLINE on July 16, 2019, updated on May 3, 2021, for French or English records. We selected studies that reported outcome from at least one domain of quality of dementia care (Access, Integration, Effective Care, Efficient Care, Population Health, Safety, and Patient-Centered) in both rural and urban persons with dementia or caregivers. We used rigorous, systematic methods for screening, selection, data extraction and we analyzed outcomes reported by at least two studies using vote counting and appraised the certainty of evidence. Finally, we explored sources of heterogeneity. Results From the 38 included studies, we found differences in many dementia care domains. Rural persons with dementia had higher mortality rates (Population Health), lower visits to any physicians (Access), more hospitalizations but shorter stays (Integration), higher antipsychotic medications (Safety), lower use of home care services and higher use of nursing home (Patient-Centered Care) compared to urban persons with dementia. Conclusions This comprehensive portrait of rural-urban differences in dementia care highlights possible geographically based inequities and can be used by researchers and decision makers to guide development of more equitable dementia care policies.